2014
DOI: 10.1111/1462-2920.12512
|View full text |Cite
|
Sign up to set email alerts
|

A genomic island integrated into recA of Vibrio cholerae contains a divergent recA and provides multi‐pathway protection from DNA damage

Abstract: Lateral gene transfer (LGT) has been crucial in the evolution of the cholera pathogen, Vibrio cholerae. The two major virulence factors are present on two different mobile genetic elements, a bacteriophage containing the cholera toxin genes and a genomic island (GI) containing the intestinal adhesin genes. Non-toxigenic V. cholerae in the aquatic environment are a major source of novel DNA that allows the pathogen to morph via LGT. In this study, we report a novel GI from a non-toxigenic V. cholerae strain con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The potential roles of two genomic islands will be examined in a future study. However, it has been shown that the inserted recA could protect against DNA damage induced by UV irradiation in V. cholerae ( 34 ). In another study, Chen et al also identified an O4:KUT-recAin type strain with an insertion of a genomic island in recA alleles, which has become a new emerging serotype since 2014 and exhibited strong acid resistance at pH 4.9 ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The potential roles of two genomic islands will be examined in a future study. However, it has been shown that the inserted recA could protect against DNA damage induced by UV irradiation in V. cholerae ( 34 ). In another study, Chen et al also identified an O4:KUT-recAin type strain with an insertion of a genomic island in recA alleles, which has become a new emerging serotype since 2014 and exhibited strong acid resistance at pH 4.9 ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This possible gene inactivation and its compensation is analogous to the method of a family of ICEs called recA -mobile elements (RME) discovered in V . cholera , which disrupt the host’s recA gene, but complement the functional loss through a divergent recA homolog embedded within the elements [ 63 ]. Sequence comparison between pSEA1 and a plasmid-like contig from V .…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the contig (named contig_8) harboring bla TEM-1 demonstrated it was 24,769 bp away (from the 3’ end of the bla TEM-1 until the 3’ end of bla PER-2) from another important β-lactamases bla PER-2. Some of the genes located in the region between bla TEM-1 and bla PER-2 where previously described in the context of genomic islands ( umuC and umuD genes) [ 46 , 47 ], or in plasmids as the genes present in the Tn 21 mer operon [ 48 ].…”
Section: Resultsmentioning
confidence: 99%